A Fast Algorithm of Moore-Penrose Inverse for the Loewner-Type Matrix. (4th January 2012) - Tong, QiuJuan; Liu, SanYang; Lu, Quan
Abstract : In this paper, we present a fast algorithm of Moore-Penrose inverse for m × n Loewner-type matrix with full column rank by forming a special block matrix and studying its inverse. Its computation complexity is O ( m n ) + O ( n 2 ), but it is O ( m n 2 ) + O ( n 3 ) by using L + = ( L T L ) − 1 L T .